Speckle interferometry at SOAR in 2019 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Costa, Edgardo; Horch, Elliott P. (The Astronomical Journal, 2020)
The results of speckle-interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2019 are given, totaling 2555 measurements of 1972 resolved pairs with separations from 15 mas (median 0.″21) and magnitude difference up to 6 mag, and non-resolutions of 684 targets. We resolved for the first time 90 new pairs or subsystems in known binaries. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. We give a list of 127 orbits computed using our latest measurements. Their quality varies from excellent (25 orbits of grades 1 and 2) to provisional (47 orbits of grades 4 and 5). © 2020 The American Astronomical Society. All rights reserved.
20 citations (Crossref) [2023-10-31] tex.ids: tokovininSpeckleInterferometrySOAR2020, tokovininSpeckleInterferometrySoar2020 tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020AJ....160....7T arXiv: 2005.05305 [astro-ph.SR] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85087554458 tex.eid: 7 type: Article
Keywords: 1081; 154; 1777; Astrophysics - Solar and Stellar Astrophysics; Binary stars; Multiple stars; Visual binary stars; dept.phy; peer-reviewed